Setting old at the urban fringe — on the relationship between suburbanisation and demographic change - Nuissl, Henning; Bigalke, Bernadett (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
German cities have experienced a vibrant process of suburbanisation in recent decades. In the face of current demographic change there is a need to reassess the phenomenon of suburbanisation in terms of how it affects the quality of life of the elderly. Based on a case study in the Leipzig urban region this paper analyses the options and opportunities of elderly suburbanites to satisfy their daily needs, maintain their social networks and pursue an independent life in their suburban living environments. At large the presented results are not suited to prove the frequently assumed negative impact of suburbanisation on the elderly.